2018
DOI: 10.1136/bmjopen-2018-021967
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fatigue and insufficient sleep on physician and patient outcomes: a systematic review

Abstract: ObjectivesFor physicians in independent practice, we synthesised evidence on the (1) impacts of insufficient sleep and fatigue on health and performance, and patient safety and (2) effectiveness of interventions targeting insufficient sleep and fatigue.DesignWe systematically reviewed online literature. After piloting, one reviewer selected studies by title and abstract; full texts were then reviewed in duplicate. One reviewer extracted data; another verified a random 10% sample. Two reviewers assessed risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
88
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 83 publications
(164 reference statements)
0
88
0
1
Order By: Relevance
“…Fatigue among doctors is also associated with less enjoyment in work [ 18 ] and high turnover intention [ 19 ]. Other consequences include adverse health and wellbeing, work-life dissatisfaction, low quality of life, job dissatisfaction, and poor skill performance [ 20 ]. On the other hand, depressed doctors have been associated with improper medical treatment and adversely affect the attitudes towards patient care [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue among doctors is also associated with less enjoyment in work [ 18 ] and high turnover intention [ 19 ]. Other consequences include adverse health and wellbeing, work-life dissatisfaction, low quality of life, job dissatisfaction, and poor skill performance [ 20 ]. On the other hand, depressed doctors have been associated with improper medical treatment and adversely affect the attitudes towards patient care [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies also demonstrated that mortality and morbidity rates were unaffected by the 2003 changes to duty hours (de Virigilio et al, 2006;Salim et al, 2007;Morrison et al, 2009). In a more recent meta-analysis, Gates et al (2018) concluded that fatigue and sleep deprivation are associated with detrimental physician health and well-being outcomes, but that there is insufficient evidence regarding the potential associations with clinical performance and patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from methodological weaknesses and heterogeneity across studies, it has also been suggested that the inconsistency of these results may reside in the ability of some physicians to compensate fatigue-related impairments (Czeisler, 2009;Sade, 2015;Gates et al, 2018). Dawson and McCulloch (2005) first introduced the notion of fatigue proofing strategies (FPS) to refer to any compensatory strategies aiming to reduce the likelihood a sleep-deprived operator will make an error.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O sono adequado traz benefícios ao funcionamento cerebral e cognição, promove aprendizado e consolidação da memória, e reestabelece processos homeostáticos, como a conexão sináptica e a restauração física (Diekelmann and Born, 2010;Walker and Stickgold, 2016 (Belenky et al, 2003). A explicação para isso é que existe uma adaptação cerebral para sustentar um desempenho estável das funções motoras, embora pouco reduzidas (Gates et al, 2018).…”
Section: Introductionunclassified